Principal Management Sekolah Umum Berbasis Pesantren (SUBP) in Strengthening Character Education of Students - Afridel DN Afridel (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
Today’s school education is faced with many issues of adolescent behavior and deviation. Several innovations are implemented in order to minimize the negative impact of adolescence, one of them through public school management based on pesantren (SUBP). The purpose of this research to describe the management of the head of the SUBP school is reviewed from the aspects of planning, organizing, actuating, and controlling. This qualitative research method uses the head of school informant, deputy head, SUBP teacher, and student. To obtain data and information, interviews, observations and documentation analysis techniques are used. The findings of this study from the aspect of planning through the integration of the curriculum with local wisdom curriculum basic religius value, on the aspect of organizing the strengthening of character education through the organization of extracurricular activities, and personal organization of character education. The aspect of actuating of character education is internalized with intra-curricular activities and extracurricular activities. Whereas the aspect of controling of character education strengthening is carried out in the form of evaluation by teachers and schools, cultivation, as well as participation of students in religious events